Bentuk Tari Munai Serapah di Sanggar Seni Sedulang Setudung Kabupaten Banyuasin (Komponen Nonverbal) - Sari, Mia Julita; NAD, Nugroho; Adoma, Auzy Madona (Indonesian Research Journal on Education, 2023)
The purpose of this study was to determine and describe the form of Munai Serapah Dance in Sedulang Setudung Art Studio, Banyuasin Regency. The method used in this research is the qualitative method. The data collection techniques in this research are observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The results showedthat the body movements in munai serapah dance use basic Malay movements that are developed and created so as to create movements and music that are in harmony without reducing the meaning of the dance conveyed. The floor patterns used in Munai Serapah dance are arrows, circular, angled, straight, "V" shape, "A" shape, and face. the makeup used in Munai Serapah dance is stage makeup. Stage makeup is makeup intended for performance.This makeup is more assertive and bold and emphasizes certain effects such as the eyes, nose, lips, and eyebrows so that special attention is drawn to the face because theface is to be seen from a distance under bright lights. The music that accompanies the Munai Serapah dance was created simultaneously with the creation of the dance. Raden Gunawan is the music director as well as the dance director of Munai Serapah dance, adjusting between dance and music, and vice versa between music and dance. Munai Serapah dance accompaniment music was created using typical Malay musical instruments and modern musical instruments but still maintains the characteristics of thick Malay music. The musical instruments used in Munai Serapah dance include drums, organ, guitar, bass, drums, and vocals.